PREDIKSI TURUNAN KESTABILAN DINAMIK WAHANA UDARA NIRAWAK HALE MENGGUNAKAN METODE BERBASIS CFD ALIRAN TAK TUNAK DAN DERET FOURIER - Fadillah, Rais
This study implements the CFD (Computational Fluid Dynamics) method to calculate the dynamic stability derivative of the HALE (High-Altitude Long Endurance) unmanned aerial vehicle. The HALE has been designed with a tandem wing configuration (front-rear) connected to three tail booms and three vertical stabilizers. This complex configuration has a unique response of aerodynamic forces and moments to external disturbances, called the dynamic stability derivative, which are required to design and analyze flight control systems. HALE carrying out surveillance and/or communication missions operating at stratospheric altitudes for a long time is required to fly autonomously with good vehicle stability. In the design, the dynamic stability characteristics can be predicted computationally by simulating an unsteady flow around the HALE which moves like a wave with a small amplitude to approximate linear motion. The motion models is applied to the simulation of the HALE vehicle in the form of translational harmonic motion (plunging oscillation) and rotational harmonic motion about the center of mass in the longitudinal direction (pitching oscillation). The unsteady flow solution is generated by solving the unsteady RANS (Reynolds Averaged Navier-Stokes) equation using dynamic grids technique. Moreover, the dynamic stability derivatives are obtained by extracting time historical data of aerodynamic forces and moments from CFD simulation using the gradient method and Fourier analysis. The validation of the static stability derivatives is carried out by comparing the results of the CFD simulation with the wind tunnel test data. Meanwhile, for the dynamic stability derivatives, it is done by comparing the results of the CFD simulation with the potential flow method (AVL program). In this study, important parameters of harmonic motion including amplitude and reduced frequency are studied.